Percepción y adaptación social frente a la variabilidad climática en el cantón Yantzaza, provincia de Zamora Chinchipe, Ecuador - Sarango Gualán, Rosa Elizabeth (2021)
The phenomena of climate variability and climate change are a challenge for planning at the global level. For Ecuador, the generation of information associated with climate variations and their impacts constitutes a challenge. However, this is possible through research, through studies of perception, beliefs and practices that the population has regarding climate variability in a given area, with which it can contribute to generate said information, in this way not it can only fill information gaps, but it also paves the way for the design of adaptation measures. In the present investigation, the objective of generating knowledge about the perception and social adaptation strategies regarding climate variability was established, which the inhabitants of the Yantzaza canton, Zamora Chinchipe province, Ecuador have developed. To obtain information, two methods were applied: i) qualitative (semi-structured interview) and ii) quantitative (meteorological data). The methodological strategy consisted of three phases: in the preliminary phase, a bibliographic review was carried out; in the field phase, semi-structured interviews were applied; and, in the office phase, the treatment of meteorological information from the National Institute of Meteorology and Hydrology (INAMHI) was carried out, and it was contrasted with the perception of the population. The results obtained show that the population is aware of the changes that the climate has presented in recent years. Your perceptions are based on personal experiences. The population has been impacted by climate variation: 41% extreme rains, 28% extreme heat, 13% extreme drought, 10% extreme cold, and 8% extreme wind. Faced with these impacts, the population has not been able to act correctly and in many cases they have not taken action; This is due to the fact that they do not have the financial resources and the information regarding the risks to which they are exposed is scarce or null. In some cases, the impacts perceived by the population are consistent with the meteorological records obtained for the sector. Based on this information, an action plan can be built to determine the vulnerability of the population to the impacts of variability. In this way, the population can be prepared and avoid future damages and losses. Keywords: Perception, climate variability, climate change, strategies, adaptation.